2018
DOI: 10.1002/1873-3468.13045
|View full text |Cite
|
Sign up to set email alerts
|

Glycan‐metabolizing enzymes in microbe–host interactions: the Streptococcus pneumoniae paradigm

Abstract: Streptococcus pneumoniae is a frequent colonizer of the upper airways; however, it is also an accomplished pathogen capable of causing life-threatening diseases. To colonize and cause invasive disease, this bacterium relies on a complex array of factors to mediate the host-bacterium interaction. The respiratory tract is rich in functionally important glycoconjugates that display a vast range of glycans, and, thus, a key component of the pneumococcus-host interaction involves an arsenal of bacterial carbohydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 207 publications
(584 reference statements)
1
46
0
Order By: Relevance
“…BgaA is regarded as a multi-functional protein and putative virulence factor; however, BgaA plays a limited or inconsequential role in in vivo colonization (King et al, 2006;Burnaugh et al, 2008;Dalia et al, 2010;Limoli et al, 2011;Singh et al, 2014;Blanchette et al, 2016;Hobbs et al, 2018). Here, we revealed that bgaA deficiency significantly reduced mortality in a mouse model of blood infection.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…BgaA is regarded as a multi-functional protein and putative virulence factor; however, BgaA plays a limited or inconsequential role in in vivo colonization (King et al, 2006;Burnaugh et al, 2008;Dalia et al, 2010;Limoli et al, 2011;Singh et al, 2014;Blanchette et al, 2016;Hobbs et al, 2018). Here, we revealed that bgaA deficiency significantly reduced mortality in a mouse model of blood infection.…”
Section: Discussionmentioning
confidence: 76%
“…BgaA also has been reported to contribute to pneumococcal adherence to host epithelial cells, host immune evasion, and in vivo biofilm formation (Dalia et al, 2010;Limoli et al, 2011;Singh et al, 2014;Blanchette et al, 2016). However, several studies reported that deletion of bgaA had limited effects on S. pneumoniae in mouse colonization models (King et al, 2006;Limoli et al, 2011;Blanchette et al, 2016;Hobbs et al, 2018). It also remains unclear if the deletion of bgaA would significantly affect host survival rate in a mouse model of sepsis.…”
Section: Bgaa Deficiency Decreases Pneumococcal Pathogenicity In a Momentioning
confidence: 99%
“…Unfortunately, we have middle ear microbiome data from only two individuals who are homozygous for p.Trp154*, but these two individuals have higher relative abundance of Streptococcaceae ( Figure S8). Interestingly, virulent strains of Streptococcus pneumoniae, a common cause of acute otitis media, use the type I operon to primarily target Lewis antigen which is regulated not only by FUT2 but also by FUT3 (MIM: 111100); 37,38 this may imply that nonsecretor status due to homozygosity for FUT2 p.Trp154* might decrease infection by other bacteria but increases predisposition to Streptococcal infection. In addition to affecting bacterial adherence, FUT2 nonsecretor status has been shown to lead to significantly greater lymphocyte infiltration during infection.…”
Section: Discussionmentioning
confidence: 99%
“…a group of reactions necessary to transition between metabolites (Richelle et al, 2020) used to describe a complete pathway of HS modification. Pathways from the Kyoto Encyclopedia of Genes and Genomes (KEGG, ec00531, (Kanehisa et al, 2017)), in combination with literature annotation of these pathways for specific bacteria (Hobbs et al, 2018;Robb et al, 2017;Ndeh et al, 2017), were used to identify reactions (enzyme commission (EC) numbers) associated with the modification task. (Table S3) Finally, we used CAZy, dbCAN, and CUPP (Barrett and Lange, 2019;Lombard et al, 2014;Yin et al, 2012;Zhang et al, 2018) to map EC numbers to microbial genes associated with glycan modification ( Table S3).…”
Section: Heparan Sulfate Modification Capability: Completeness and Camentioning
confidence: 99%